2016
DOI: 10.1002/chem.201602518
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Constrained Peptidomimetics as Inhibitors of the Protein Arginine Methyl Transferases

Abstract: Protein arginine N-methyl transferases (PRMTs) belong to a family of enzymes that modulate the epigenetic code through modifications of histones. In the present study, peptides emerging from a phage display screening were modified in the search for PRMT inhibitors through substitution with non-proteinogenic amino acids, N-alkylation of the peptide backbone, and incorporation of constrained dipeptide mimics. One of the modified peptides (23) showed an increased inhibitory activity towards several PRMTs in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…Moreover, insertion of this constraint restrains the ψ backbone torsion angle to around 180°, which obviously orients the peptide main chain. We have previously shown that constrained indoloazepinones, when incorporated in peptide sequences, induce C 7 ‐turns (or γ‐turns), stabilized by hydrogen bonds and aromatic π‐stacking interactions, in [D 3 ]methanol and phosphate buffer at 20 °C . In this context, we expected that oligomers based on repetitive l ‐Aia‐Xxx dipeptides might adopt discrete structures that would be able to favor their cell‐penetrating properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, insertion of this constraint restrains the ψ backbone torsion angle to around 180°, which obviously orients the peptide main chain. We have previously shown that constrained indoloazepinones, when incorporated in peptide sequences, induce C 7 ‐turns (or γ‐turns), stabilized by hydrogen bonds and aromatic π‐stacking interactions, in [D 3 ]methanol and phosphate buffer at 20 °C . In this context, we expected that oligomers based on repetitive l ‐Aia‐Xxx dipeptides might adopt discrete structures that would be able to favor their cell‐penetrating properties.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that constrained indoloazepinones,w hen incorporated in peptide sequences, induce C 7 -turns( or g-turns [29] ), stabilized by hydrogen bonds and aromatic p-stacking interactions, in [D 3 ]methanola nd phosphate buffer at 20 8C. [30] In this context, we expected that oligomers based on repetitive l-Aia-Xxx di-peptidesm ight adopt discrete structures that would be able to favor their cell-penetrating properties. Indeed,i th as been demonstrated that secondary structures of CPPs werea ble to control their cellularu ptake to ac ertain extent, and were crucial in many cases.…”
Section: Conformation Analysismentioning
confidence: 99%
“…Notable is the use of l ‐Aia residues in the development of protein arginine methyltransferase (PRMT) inhibitors (Fig. ) [Knuhtsen et al, ]. Introduction of cyclic constraints by N‐to‐C, N‐to‐sidechain, sidechain‐to‐C, and sidechain–sidechain bonds render peptides and small proteins resistant to proteolytic degradation as well as impacting relative sidechain orientation through preorganization.…”
Section: Synthetic Tools For Preorganizationmentioning
confidence: 99%
“… Insertion of constrained tryptophan residues mimics ( l ‐Aia), was found to determine a pseudo‐ring turn structure with a consequent increased potency against PRMTs. Reproduced from Knuhtsen et al [].…”
Section: Synthetic Tools For Preorganizationmentioning
confidence: 99%
“…PRMT inhibitors reported to date can be broadly categorised into SAM analogues (including the panmethyltransferase inhibitors sinefungin (3) and S-adenosyl homocysteine (2), ( Figure 1A)), substrate peptide analogues [25][26][27][28], and structures optimised from high throughput screening hits [29][30][31][32]. Promising CARM1 inhibitors include EPZ022302/EZM2302 (a 6 nM CARM1 inhibitor with anti-tumour activity in vivo) [23] and TP-064 (IC 50 < 10 nM against CARM1 and >100-fold selective over other methyltransferases) [32].…”
Section: Introductionmentioning
confidence: 99%